Kidney Cancer and Potential Use of Urinary Extracellular Vesicles - Linh Nguy-Hoang Le; Linh Nguy-Hoang Le; Javaria Munir; Eun-Bit Kim; Seongho Ryu; Seongho Ryu (Frontiers Media S.A., 2024)
Kidney cancer is the 14th most common cancer globally. The 5-year relative survival rate of kidney cancer at a localized stage is 92.9% and it declines to 17.4% in metastatic stage. Currently, the most accurate method of its diagnosis is tissue biopsy. However, the invasive and costly nature of biopsies makes it undesirable in many patients. Therefore, novel biomarkers for diagnosis and prognosis should be explored. Urinary extracellular vesicles (uEVs) are small vesicles (50-200 nm) in urine carrying nucleic acids, proteins and lipids as their cargos. These uEVs' cargos can provide non-invasive alternative to monitor kidney health. In this review, we have summarized recent studies investigating potential use of uEVs' cargos as biomarkers in kidney cancer for diagnosis, prognosis and therapeutic intervention.